IMPLEMENTASI PEMBUATAN KARTU IDENTITAS ANAK (KIA) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KECAMATAN MIJEN KOTA SEMARANG - Dandi Imannullah; Nina Widowati (Journal of Management and Public Policy, 2026)
The Child Identity Card (Kartu Identitas Anak/KIA) is a government policy to fulfill children’s civil rights and strengthen orderly population administration, as regulated in the Minister of Home Affairs Regulation No. 2 of 2016. It mandates local governments through the Population and Civil Registration Office (Disdukcapil) to provide KIA services for children from birth until one day before turning 17. This study analyzes the implementation of KIA issuance in Kecamatan Mijen, Kota Semarang, and identifies supporting and inhibiting factors. Using a descriptive qualitative approach with interviews, observations, and documentation, the findings show that KIA services have been implemented according to procedures and regulations, yet ownership in Mijen remains relatively low compared to other districts. Key obstacles include low public awareness of KIA’s urgency, uneven outreach, limited human resources and facilities, and social-geographic conditions affecting service coverage. Many parents still view KIA as a supplementary document processed only when needed for administrative purposes, such as school enrollment. Therefore, improving implementation requires stronger outreach, increased resource capacity, and better cross-sector coordination to reach targets more evenly and sustainably.